Making places: the role of attachment in creating the sense of place for traditional streets in Malaysia - Shamsuddin, Shuhana (Pergamon Press, 2008)
Sense of place definition includes the point where the physical element, activity and meaning are intertwined in the people experience of place. In urban design and place quality research, much has been discussed on the significance of the physical elements and activities in creating the sense of place; however, the role of place attachment as a component that gives places meaning(s) has not been adequately explored. This article is based on the main findings of a doctoral research examining attachment to traditional shopping streets in the city centre of Kuala Lumpur. Surveys and face-to-face interviews were conducted with users of the streets to investigate place attachment and its influence on place identity. The finding demonstrates that attachment to the traditional streets is strong and it influences the users' perception on the identity of the places. The streets were regarded as very important in sustaining the economic activities and meaningful in accentuating cultural diversity and self and group identity. The historical significance of the area as the earliest shopping locations in the city evoked personal and shared meanings to the long-term users who developed stronger place attachment. The paper concludes by establishing that place attachment has a significant contribution to the sense of place therefore should be considered in the design of urban places especially when redevelopment is one of the options.